(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2024)
The productivity of an organization's workforce has a significant role in its performance, which determines its survival and growth. Organizations nowadays have a lot of unattended issues relating to employee productivity. One of these issues is the inability to guarantee and give a positive and suitable work environment for the employees. The physical features of the workplace are just as important in maintaining expected labor productivity. This research study is raised to investigate how a conducive office physical environment impacts employee’s motivation and productivity. The majority of employees acknowledge that their present workplace's physical environment has a significant impact on their level of productivity and motivation to perform. Additionally, the employees perceived that there were serious problems with office layout, desk management, ventilation, workspace, ergonomics, and document storage capacity. It also revealed that there are unlabeled documents, cabinets, and drawers, or they contain undetectable information that is difficult to recognize and causes it to be inefficient, and finding documents or files, whether they be in physical or digital format, is a problem in the workplace. The results demonstrated that an organization needs to enhance its physical working environment in order to persuade people to remain in the office and be productive. The researchers recommend that Bestlink College of the Philippines' Accounting Department improve its office layout by implementing the 5S system for office management (sort, set in order, shine, standardize, and sustain). These procedures entail going over each object in a room, evaluating what is and isn't necessary, organizing everything, cleaning, and establishing protocols for executing these duties on a regular basis.